Prevalence and predictors of Sickle Cell Nephropathy A single-center experience - Khaled Elzorkany; Mortadah Alsalman; Muthana AlSahlawi; Azam Alhedhod; Nasser Abdullah Almulhim; Nora Jalal Alsultan; Eman Mohammed Al-Ali; Eman Ali; Nawal Eltayeb Omer (Scientific Reports)
Abstract Sickle cell disease (SCD) is the most common monogenic disorder in Saudi Arabia, which associates with an increased risk of organs damage, including the kidney. The aim of this study is to investigate the prevalence and predictors of sickle cell nephropathy (SCN) in the Saudi population. A retrospective study was conducted from April to October 2023, and included 343 adult patients with SCD who were recruited from the hereditary blood diseases center (HBDC), Al-Ahsa, Saudi Arabia. Spot protein-to-creatinine ratio was measured and glomerular filtration rate (GFR) was estimated from serum creatinine using the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation. As per KIDGO guidelines, CKD was diagnosed in 93 (27.1%) patients. Based on the CKD-EPI equation, 2% of patients had low GFR (eGFR < 60mL/min), 28.3% had high GFR (eGFR > 140 mL/min), and 69.7% had normal GFR. Among SCD patients, proteinuria was observed in 26.5% of the patients. SCD patients with CKD were significantly older than non-CKD patients (p < 0.001) and had higher prevalence of diabetes mellitus (DM) and hypertension (HTN) (p = 0.045 and 0.001 respectively). The multivariate analysis showed that age (P = 0.001; OR 1.035; 95% CI 1.014–1.056) and low hemoglobin level (p = 0.034; OR -0.851; 95% CI 0.721–0.980) were independent risk factors for the development of SCN. Nephropathy is a common complication among patients with SCD as early as the third decade of life, although they remain asymptomatic. Advances in age and low hemoglobin levels are the main predictors of nephropathy. In addition, SCD patients with coexistent comorbidities, particularly DM and HTN, were at increased risk of developing kidney disease.